PECTORALIS MAJOR TENDON INJURY: RECONSTRUCTION USING BONE TUNNEL AND ANCHORS - JOSÉ CARLOS GARCIA JUNIOR; EDUARDO FERREIRA CORDEIRO; HILTON VARGAS LUTFI; MAURÍCIO DE PAIVA RAFFAELLI; MAURÍCIO SALOMÃO FADEL; MÁRCIO EDUARDO KOZONARA (Acta Ortopédica Brasileira, 2022)
ABSTRACT Objective: This study aims to assess a new technique used for pectoralis major reconstruction using bone tunnel and fixation with metallic anchors in the contralateral cortical bone. Methods: Patients who had undergone post-surgical reconstruction of the pectoralis major at least 24 months before were assessed by the UCLA Shoulder Score and the Simple Shoulder Test and compared with the contralateral side by manual goniometry. Subgroup analysis was also performed between grafted and non-grafted patients. Results: 13 patients fulfilled the inclusion criteria. The average UCLA score was 34.77 ± 0.12, compared with the standard 27 of good and excellent results p < 0.0001. The Simple Shoulder test mean was 11.92 ± 0.08. Grafted and non-grafted subgroups had no statistical differences for UCLA p = 0.58 and Simple Shoulder Test p = 1.00. Long term losses for elevation or external rotation were lower than 5º. No lesions recurred. All patients returned to their physical activities with no restrictions. Conclusion: The pectoralis major reconstruction technique using a bone tunnel and metallic anchors in the contralateral cortical bone was effective. However, its execution needs special care to avoid complications. Level of Evidence IV, Case Series.